2021
DOI: 10.1007/s10518-021-01248-0
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of strengthened masonry structures: actual behaviour of buildings in Norcia and Campi Alto during the 2016 Central Italy seismic sequence

Abstract: The structural response of unreinforced masonry buildings designed for gravity load only or with reference to obsolete seismic provisions is widely studied in the literature in order to define proper strengthening strategies and solution to mitigate the seismic risk. However, the critical analysis of the effectiveness of past used strengthening solution is still lacking. To fill such gap, the present study deals with the evaluation of the seismic performances of buildings in Campi Alto struck by the 2016 centr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Past experiences have demonstrated that piecemeal interventions very often fail to address the complex requirements for safer, more energy-efficient and sustainable existing building stock [16]. Even though this has been the most common approach for retrofitting and remains the most widespread practice in the construction sector, recent extreme events (e.g., the earthquakes in southern Europe such as L'Aquila 2009 [17], Emilia 2012 [18] and Central Italy 2016 [19]) have highlighted its limitations and disadvantages. Collapses after earthquakes or the inadequacy of non-integrated retrofitting interventions showed how greatly they can reduce the effectiveness of the refurbishment, in many cases not allowing for a suitable functionality of the building.…”
Section: Introductionmentioning
confidence: 99%
“…Past experiences have demonstrated that piecemeal interventions very often fail to address the complex requirements for safer, more energy-efficient and sustainable existing building stock [16]. Even though this has been the most common approach for retrofitting and remains the most widespread practice in the construction sector, recent extreme events (e.g., the earthquakes in southern Europe such as L'Aquila 2009 [17], Emilia 2012 [18] and Central Italy 2016 [19]) have highlighted its limitations and disadvantages. Collapses after earthquakes or the inadequacy of non-integrated retrofitting interventions showed how greatly they can reduce the effectiveness of the refurbishment, in many cases not allowing for a suitable functionality of the building.…”
Section: Introductionmentioning
confidence: 99%
“…7 New earthquake hazard map of Turkey [8] investigated. Sisti et al [36] investigated the response of buildings in Campi Alto which was strengthened in the past 30 years after the 2016 Central Italy seismic sequence. According to the visual inspections carried out after the 2016 seismic sequence, they obtained that he behavior of buildings in Campi Alto was not satisfactory.…”
Section: Introductionmentioning
confidence: 99%